Тоталитарные угрозы в информационном обществе - Денисенко, Д. А. (ХНУРЭ, 2012)
In the given work problems of totalitarianism in the modern world are considered. Is carried out the analysis of modern culture and its suitability as base to modern totalitarianism. A modern quality monitoring behind the population are considered.